2018
DOI: 10.29244/jekp.5.1.63-89
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengembangan Ekspor Kopi Di Indonesia

Abstract: This study aims to analyze recommendations that Indonesia could undergo to increase it’s coffee export performance through factors influencing it’s coffee export growth driver. The analysis using export decomposition showed that since 1994-2013, Indonesian coffee export has been dominated by commodity (grean bean). Export in the form of commodity is fragile regarding it’s volatile price in the international market. This lead to recommend higher processed coffee incorporated in Indonesian coffee export structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
0
10
0
10
Order By: Relevance
“…The means that can be utilized in order to improve indonesia's coffe competitiveness were productivity and quality increasing based on speciality (Jamil, 2019) and must directly proportional to government policies that continue support the export of Indonesian coffee beans in the global market (Alexander and Nadapdap, 2019). Moreover, The development of the coffee processing industry can be one of the steps to increase the selling value of Indonesian coffee in the world (Sahat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The means that can be utilized in order to improve indonesia's coffe competitiveness were productivity and quality increasing based on speciality (Jamil, 2019) and must directly proportional to government policies that continue support the export of Indonesian coffee beans in the global market (Alexander and Nadapdap, 2019). Moreover, The development of the coffee processing industry can be one of the steps to increase the selling value of Indonesian coffee in the world (Sahat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lukman (2012) confirmed that the demand for Indonesia coffee export varied with an average of 6.17% to the United States for the period of 1985 until 2009. Sahat et al (2016) mentioned that Indonesia coffee exports were still dominated by coffee beans in the period of 1994 until 2013. Internationally, the coffee bean price as a commodity fluctuated and was easily influenced by the market condition.…”
Section: The Growth Analysis Of Factors Contributing To the Cev From mentioning
confidence: 99%
“…Namun, sebagian besar produksi kopi di Indonesia adalah untuk diekspor. Volume biji kopi yang diekspor pada bulan September 2016 adalah sebesar 267.058 ton, yaitu sekitar 40% dari total produksi kopi (Kustiari, 2016;Sahat et al, 2016).…”
Section: Pendahuluanunclassified